Psychological background of the internal picture of the disease in patients with multiple sclerosis - Simonenko Григорій (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific and practical conference with international participation "Psychosomatic medicine: science and practice". It is dedicated to the psychological background of the internal picture of the disease in patients with multiple sclerosis.